Structure and luminescence of Eu3+-doped class I siloxane-poly(ethylene glycol) hybrids - Molina, C.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Craievich, A. F.; Ribeiro, SJL (Amer Chemical Soc, 2001)
Transparent, flexible, and luminescent EU3+-doped siloxane-poly(ethylene glycol) (PEG) nanocomposites have been obtained by the sol-gel process. The inorganic (siloxane) and organic PEG phases are usually linked by weak bonds (hydrogen bonds or van der Waals forces), and small-angle X-ray scattering (SAXS) measurements suggest that the structure of these materials consists of fractal siloxane aggregates embedded in the PEG matrix. For low Eu3+ contents, n = 300 and n = 80, the aggregates are small and isolated and their fractal dimensions are 2.1 and 1.7, respectively. These values are close to those expected for gelation mechanisms consisting of reaction-limited cluster-cluster aggregation (RLCCA) and diffusion-limited cluster-cluster aggregation (DLCCA). For high Eu3+ content, SAYS results are consistent with a two-level structure: a primary level of siloxane aggregates and a second level, much larger, formed by the coalescence of the primary ones. The observed increase in the glass transition temperature for increasing Eu3+ content is consistent with the structural model derived from SAXS measurements. Extended X-ray absorption fine structure (EXAFS) and luminescence spectroscopy measurements indicate that under the experimental conditions utilized here Eu3+ ions do not strongly interact with the polymeric phase.